If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2(-6.5) = 4 Multiply -2 * -6.5 x + 13 = 4 Reorder the terms: 13 + x = 4 Solving 13 + x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + x = 4 + -13 Combine like terms: 13 + -13 = 0 0 + x = 4 + -13 x = 4 + -13 Combine like terms: 4 + -13 = -9 x = -9 Simplifying x = -9
| 0.14(y-7)+0.20y=0.06y-2.8 | | -2(5+6m)+16=p-90 | | a/b1cd | | -112=4(4x+4) | | 3.7+10m=7.18 | | 2(x+1)-3x=6 | | 5(x+4)=7(x-7)+10 | | 55=18x+y | | H=7/6(a-9) | | -105=3(5b+5) | | 7x-2x+2=x-4+6 | | A=7/6(h-9) | | -8/10-4/5 | | 4w^2-5w-4w^2+20w=w-5 | | -3(7x+5)=132 | | X-3/3/4=1/18 | | 4w^2-5w-4w^2+20w=w-4 | | -30x=78 | | 96=4(4b-4) | | 7/3=84/x | | -28-7k=5(-5k-2) | | x+6y=1fory | | X-2/1/4=1/18 | | B+2x=cx | | -15=8v+7v | | 5x-2y=-2a | | X-2/1/4 | | 14x(3+7)=46 | | -5y+3y+10=36 | | 21x^2+6+33x=0 | | -8p-32=-4(6p-4) | | 1/4x-1=1/2x-8 |